Wheat, barley and corn silage rations and urea for growing steers - K. Bolsen; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1976)
Eight rations were fed to 15 yearling steers (3 pens of 5 steers each). Arthur wheat, Paoli barley and corn silages were supplemented with either soybean meal or urea; Blue Boy II and Eagle wheat silages were supplemented with soybean meal. All steers were full-fed a 12.5% crude protein ration containing 86% silage and 14% supplement. Results of the 84-day trial show steers fed the four corn and barley silage rations gained faster and more efficiently than those fed wheat silages. Steers fed Arthur and Eagle silage rations performed similarly. Those fed Blue Boy II silage made the slowest and least efficient gain. Steers receiving urea performed similarly to those receiving soybean meal.
Keywords: Cattlemen' s Day; 1976; Report of progress (Kansas State University. Agricultural Experiment Station); 262; Beef; Wheat; Barley; Corn silage; Urea; Steers